Haploidentical Hematopoietic Cell Transplantation Using Posttransplant Cyclophosphamide for Sézary Syndrome - Kanda-Kato, Madoka (Case Rep Oncol, 2020)
Patients with advanced-stage mycosis fungoides (MF) and Sézary syndrome (SS) have a poor prognosis. Allogeneic hematopoietic cell transplantation (HCT) is a potentially curative treatment option; however, since most patients with MF/SS are elderly, they often have difficulty in finding HLA-matched donors. In recent years, HCT from HLA-haploidentical donors (haplo-HCT) using posttransplant cyclophosphamide (PTCy) as graft-versus-host disease prophylaxis has been conducted for patients without HLA-matched donors. Infectious complications, particularly cutaneous bacterial infections, are common among patients with MF/SS. The lower incidence of severe infectious complications after haplo-HCT than after an unrelated cord blood transplantation could lead to lower transplant-related mortality. Here, we report on a patient with SS who was treated successfully with haplo-HCT with PTCy. The patient has remained in complete remission for more than 24 months.